2009
DOI: 10.1111/j.1530-0277.2009.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Alcohol: Do Outlets Play a Role?

Abstract: Background The purpose of this study was to determine whether the number of alcohol outlets in local and adjacent areas, in particular bars, was related over time to completed suicide and suicide attempts. There is evidence both from studies of individuals and time series aggregate studies, mostly at the national level, of substantial alcohol involvement in suicide, but no small-area, longitudinal studies have been carried out. The present study is the first that is both longitudinal and based on a large numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 48 publications
4
32
0
1
Order By: Relevance
“…Yet no association was detected between outlet density and young female suicide mortality in the study. Another study by Johnson and colleagues (2009) conducted a repeated cross-sectional analysis with a spatial random effects model on zip code-level suicide rates in California from 1995 to 2000 to evaluate the impact of outlet density. They found that death by suicide rates were higher in zip code areas with greater local and lagged bar densities, and higher in areas with greater local but not lagged off-premise outlet densities (e.g., liquor stores).…”
Section: Resultsmentioning
confidence: 99%
“…Yet no association was detected between outlet density and young female suicide mortality in the study. Another study by Johnson and colleagues (2009) conducted a repeated cross-sectional analysis with a spatial random effects model on zip code-level suicide rates in California from 1995 to 2000 to evaluate the impact of outlet density. They found that death by suicide rates were higher in zip code areas with greater local and lagged bar densities, and higher in areas with greater local but not lagged off-premise outlet densities (e.g., liquor stores).…”
Section: Resultsmentioning
confidence: 99%
“…1 Suicide is among the leading types of injury mortality linked with alcohol consumption. 2 Most investigations of the alcohol-suicide relationship have examined the role of long-term patterns of alcohol use and related problems, including population studies of alcohol consumption or availability and suicide rates 35 and individual-level studies of the risk for suicide associated with alcohol use disorder. 68 There are more limited data on acute use of alcohol before suicide, although available data indicate that it plays a significant role.…”
mentioning
confidence: 99%
“…Previous studies have pointed to a positive association between alcohol outlet density and suicide rates (15, 19, 25, 26). Escobedo and Ortiz (26) examined data from New Mexico for 1990 to 1994 and found that as outlet density increases so do suicides and alcohol-related crashes, reporting that these associations continued to be statistically significant when they considered the effects of age, sex and minority status.…”
Section: Introductionmentioning
confidence: 94%
“…Studies focusing at the population level have shown that alcohol consumption (1014) outlet density (15), price (16), and sales (17–19) are associated with increased suicide rates. There is substantial international evidence over several decades indicating that alcohol outlet density is associated with a range of alcohol-related harms including suicide (8, 20–23).…”
Section: Introductionmentioning
confidence: 99%